Decay of Low-Barrier Metastable State: Middle Friction; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Aktaev N. E. Nurken Erbolatovich (Numerical Simulation of Physical and Chemical Processes, 2016)
Title screen